Diagnostic accuracy of 14‐3‐3 η protein in rheumatoid arthritis: A meta‐analysis. (10th September 2020) - Wang, Decai; Cui, Yalan; Lei, Huiren; Cao, Ding; Tang, Guoting; Huang, Haiming; Yuan, Ting; Rao, Lizong; Mo, Biwen
Abstract: Aim: To evaluate the overall diagnostic performance of 14‐3‐3 η protein in patients with rheumatoid arthritis (RA). Methods: PubMed, EMBASE, and Web of Science were searched to acquire eligible studies. Articles published in English before 20 February 2020 were included. Quality Assessment of Diagnostic Accuracy Studies 2 was used to evaluate the risk of bias and application concern of the included articles. Pooled analysis of diagnostic indicators of 14‐3‐3 η protein for RA was conducted by using a random effects model. Subgroup analysis was used to explore the sources of heterogeneity. Deeks' funnel plot asymmetry test was used to evaluate for the presence of publication bias. Results: A total of 13 studies (1554 positive and 1934 negative participants) were included. The pooled sensitivity and specificity were 0.73 (95% CI 0.71‐0.75) and 0.88 (95% CI 0.87‐0.90), respectively. The pooled positive/negative likelihood were 5.98 (95% CI 4.39‐8.14) and 0.28 (95% CI 0.21‐0.37), respectively. In addition, the pooled diagnostic odds ratio was 23.48 (95% CI 13.76‐40.08) and the area under curve was 0.9245. The results of subgroup analysis indicated that ethnicity and control group might be the source of heterogeneity. The results of sensitivity analysis were stable. No significant publication bias was found. Conclusions: The current evidence indicated that 14‐3‐3 η protein has moderate accuracy for the diagnosis of RA.